2018
DOI: 10.1002/ijc.31787
|View full text |Cite
|
Sign up to set email alerts
|

Reliable identification of women with CIN3+ using hrHPV genotyping and methylation markers in a cytology‐screened referral population

Abstract: Cervical screening aims to identify women with high-grade squamous intraepithelial lesion/cervical intraepithelial neoplasia 2-3 (HSIL/CIN2-3) or invasive cervical cancer (ICC). Identification of women with severe premalignant lesions or ICC (CIN3+) could ensure their rapid treatment and prevent overtreatment. We investigated high-risk human papillomavirus (hrHPV) detection with genotyping and methylation of FAM19A4/miR124-2 for detection of CIN3+ in 538 women attending colposcopy for abnormal cytology. All wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 41 publications
3
18
0
1
Order By: Relevance
“…A total of 538 women had a smear which was eligible for methylation testing and interpretation of the result . Of these women, 482 remained after exclusion of biopsies which had a worst diagnosis on the newly sectioned slide which was more than 1 grade aside from the consensus diagnosis on the locally produced histology slide.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 538 women had a smear which was eligible for methylation testing and interpretation of the result . Of these women, 482 remained after exclusion of biopsies which had a worst diagnosis on the newly sectioned slide which was more than 1 grade aside from the consensus diagnosis on the locally produced histology slide.…”
Section: Resultsmentioning
confidence: 99%
“…Residual material after HPV testing and cytology was concentrated and sent to DDL Diagnostic Laboratory for methylation testing . DNA was isolated using the MagNA Pure 96.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation assays on the other hand recorded sensitivity, specificity, PPV, NPV, and AUC ranges of 59.7-92.9%, 67-98%, 15-95.4%, 65.5-98.3%, and 0.81-0.86, respectively, in detection of CIN2+ [23,[38][39][40][41][42][43][44], with a low sensitivity of 59.7% reported by Schmitz et al [23], compared to 92.9% sensitivity by Dong et al [39]; and extreme PPV of 15% reported by van Leeuwen et al [40], compared to 95.4% PPV by Kong et al, [38]. DNA methylation is a major epigenetic mechanism that involves the transfer of a methyl group to the C5 carbon residues (5mC) of cytosines that is mediated by a family of DNA methyltransferases, and plays an important role in various biological processes including the regulation of gene expression, genomic imprinting, cell differentiation, development, and inflammation [70].…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation of CpG islands in the promoter regions of tumor suppressor genes leads to silencing of the gene and is an essential step in the development of many cancers, including CC [8]. Hypermethylation of promoter regions in certain genes has also been suggested as a molecular alteration appearing in transforming HSIL/CIN2-3 lesions at high risk of progression to CC [9,10,11,12,13,14]. Recent studies have shown that the combination of methylation-mediated silencing of CADM1 (cell adhesion molecule 1) and MAL (T-lymphocyte maturation-associated protein) promoter genes in cervical scrapes seems to be related to the duration of hrHPV infection and the severity of the SIL/CIN lesion [10,15].…”
Section: Introductionmentioning
confidence: 99%